Kemampuan Guru IPA Kelas VII dalam Penyusunan dan Pelaksanaan RPP Berdasarkan Kurikulum 2013 di SMP Negeri se-Kabupaten Boyolali Semester Genap Tahun Ajaran 2014/2015 - Hidayati, Yuli, Drs. Djumadi, M.Kes (2015)
The lesson plans describing the procedures and management which is used by every lecturers as a general guide to implement learning. The purpose of this research is to know the ability of seventh grade science teacher in the preparation of lesson plan at SMPN of Boyolali on 2nd semester academic year 2014/2015 and conformity of learning implementation with curriculum 2013. This research conducted in SMPN 1 Boyolali, SMPN 1 Ampel, and SMPN 1 Sawit. The subject of this research is seventh grade science teacher at SMPN of Boyolali on 2nd semester academic year 2014 / 2015. The object of this research is the lesson plans prepared by seventh grade science teacher at SMPN of Boyolali on 2nd semester academic year 2014 / 2015. The kind of this research is qualitative descriptive. techniques of data collection is done by way of documentation, observation, and an interview. The result showed that the ability of seventh grade science teacher in the preparation of lesson plan based on curriculum 2013 at SMPN of Boyolali on 2nd semester academic year 2014/2015 including the excellent category (84.3%) with the percentage of school teacher's A (86.4%), school teacher,s B (80.3% ), school teacher's C (86.3%). Suitability learning implementation of seventh grade science teacher at SMPN of Boyolali on 2nd semester academic year 2014/2015 amounted to 88% (excellent) with the percentage of school teacher's A (93.7%), school teacher's B (76.6%), and school teacher's C (93.7%).